Influenza-associated mortality in temperate and subtropical chinese cities, 2003-2008 - Luzhao Feng; David K Shay; Yong Jiang; Hong Zhou; Xin Chen; Yingdong Zheng; Lili Jiang; Qingjun Zhang; Hong Lin; Shaojie Wang; Yanyan Ying; Yanjun Xu; et al. (The World Health Organization, 2012)
OBJECTIVE: To estimate influenza-associated mortality in urban China. METHODS: Influenza-associated excess mortality for the period 2003-2008 was estimated in three cities in temperate northern China and five cities in the subtropical south of the country. The estimates were derived from models based on negative binomial regressions, vital statistics and the results of weekly influenza virus surveillance. FINDINGS: Annual influenza-associated excess mortality, for all causes, was 18.0 (range: 10.9-32.7) deaths per 100000 population in the northern cities and 11.3 (range: 7.3-17.8) deaths per 100000 in the southern cities. Excess mortality for respiratory and circulatory disease was 12.4 (range: 7.4-22.2) and 8.8 (range: 5.5-13.6) deaths per 100000 people in the northern and southern cities, respectively. Most (86%) deaths occurred among people aged >65 years. Influenza-associated excess mortality was higher in B-virus-dominant seasons than in seasons when A(H3N2) or A(H1N1) predominated, and more than half of all influenza-associated mortality was associated with influenza B virus. CONCLUSION: Between 2003 and 2008, seasonal influenza, particularly that caused by the influenza B virus, was associated with substantial mortality in three cities in the temperate north of China and five cities in the subtropical south of the country.